Challenges in the clinical development of PI3K inhibitors. (28th March 2013) - Massacesi, Cristian; di Tomaso, Emmanuelle; Fretault, Nathalie; Hirawat, Samit
Abstract : The PI3K/Akt/mTOR pathway is one of the most frequently dysregulated signaling pathways in cancer and an important target for drug development. PI3K signaling plays a fundamental role in tumorigenesis, governing cell proliferation, survival, motility, and angiogenesis. Activation of the pathway is frequently observed in a variety of tumor types and can occur through several mechanisms. These mechanisms include (but are not limited to) upregulated signaling via the aberrant activation of receptors upstream of PI3K, amplification or gain‐of‐function mutations in the PIK3CA gene encoding the p110α catalytic subunit of PI3K, and inactivation of PTEN through mutation, deletion, or epigenetic silencing. PI3K pathway activation may occur as part of primary tumorigenesis, or as an adaptive response (via molecular alterations or increased phosphorylation of pathway components) that may lead to resistance to anticancer therapies. A range of PI3K inhibitors are being investigated for the treatment of different types of cancer; broad clinical development plans require a flexible yet well‐structured approach to clinical trial design.